Triage by cervical length sonographic measurements for targeted therapy in threatened preterm labor: A double blind randomized clinical trial - Homeira Vafaei; Neda Rahimirad; Seyedeh Marjan Hosseini; Maryam Kasraeian; Nasrin Asadi; Hadi Raeisi Shahraki; Khadijeh Bazrafshan (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Preterm labor and birth are associated with several neonatal complications including respiratory distress syndrome and intraventricular hemorrhage. Differentiating true and false labor pain is a dilemma to obstetricians. Objective: To elucidate the role of cervical length measurement in prediction of birth in pregnant women with threatened preterm labor. Materials and Methods: In this double blind randomized clinical trial, 120 women with gestational age <34 wk who presented painful uterine contractions randomly assigned to undergo measurement of cervical length. Patients were registered in the hospital and a unit number was given. Based on the unit numbers, patients were randomly assigned to two groups using a computerized random digit generator. All participants were managed accordingly (n=65) or to receive tocolysis as planned (n=55). Tocolysis was prescribed when cervical length was <15 mm while those with cervical length ≥15 mm were managed expectantly. Delivery within 7 days of the presentation was the primary outcome. Results: This RCT showed in case group, 78.9% of patient with cervical length <15 mm were delivered within 7 days and only 21.1% of them maintained their pregnancy. Of those with cervical length ≥15 mm, only 15.2% were delivered within the study period and the rest (84.8%) maintained their pregnancy (p<0.001). Conclusion: “Our results indicate that in women who presented preterm labor symptoms, cervical length measurement will result in decreased unnecessary tocolytic treatment. Women with cervical length ≥15mm should not receive tocolysis, however, withholding corticosteroid therapy in these patients needs further evidence.